Minat Belajar Dasar Akuntansi Keuangan I Ditinjau Dari Persepsi Mahasiswa Mengenai Kompetensi Dosen Dan Pola Belajar Pada Mahasiswa Program Studi Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2014/2015 - SETYANINGSIH, INDRI AVISHA, Drs. H. Sudarto, HS., M.M (2015)
The purpose of this study was to determine the effect of: 1) the perception of students about the competence of lecturers to the interest in learning Basic Financial Accounting I; 2) study the pattern of the interest in learning Basic Financial Accounting I; 3) perceptions of students about the competence of lecturers and learning patterns of the interest in learning Basic Financial Accounting I. This research is a quantitative associative. The population in this study were students of Accounting Education FKIP 2014/2015 UMS force numbering 237 with 142 samples taken by random sampling technique-incidental sampling. Data collection techniques using methods of documentation and questionnaires that have been tested with the validity and reliability test. Data analysis technique used is multiple linear regression, t test, F test, test R2, the relative contribution and effective contribution. Results of the analysis of the data shows a linear line equation Y = 71.734 + 0,272X1 + 0,365X2. The conclusion is 1) Perceptions of students regarding the competence of lecturers positive effect on interest in learning. This is evident from the results of ttest students who obtain tcount perception regarding the competence of lecturers (X1) of 2.116> t table (1.977) and significance value 0.036 <0.05; 2) The pattern learning positive influence on interest in learning. This is evident from the results of the t test variable gain tcount learning patterns (X2) of 2.803> t table (1.977) and significance value 0.006 <0.05; 3) Perceptions of students regarding the competence of lecturers and learning patterns together positive effect on interest in learning. This is evident from the test results that obtain Fcount F> F table (82.846> 3.061) and significance value of 0.000 <0.05; 4) The perception of the students regarding the competence of lecturers (X1) relative contribution of 42.7% and the effective contribution of 23.2%. While the calculation of the variable patterns of learning (X2) the relative contribution of 57.3% and the effective contribution of 31.2%. 5) R2 calculation results obtained 0,544 , which means 54.4 % interest in learning is influenced by the perceptions of students about the competence of lecturers and learning patterns , the remaining 45.6 % is influenced by other variables outside the research . Keywords : Perception students about the competence of lecturers, learning patterns, interest in learning.